Altar Space in Late Antiquity: The Water Newton Treasure and the Construction of the Sacred Space - Samaretz, Nicolas (Eikón / Imago, 2026)
Dated between the second half of the 4th and the early 5th centuries CE, the Water Newton treasure is the earliest material example of a liturgical and votive Christian hoard. Previous research has focused on determining the overall function and the treasure’s possible original context. This article presents an overview of the treasure’s components from the perspective of their relation to the Christian altar, mainly during the Eucharist. After examining the liturgical paraphernalia and furnishings in the 4th and 5th centuries, as documented by late antique church inventories, the individual objects are studied in their ritual application. This lets us appreciate the role of material culture in defining the sacred space. The continuity with ancient traditions emerges, such as certain vessels’ connection with some substances and properties or the adoption of ritual practices, reinterpreted through a new Christian meaning. Starting from the material analysis and the written evidence, the article aims to frame the treasure in the wider perspective of Christian altar space development. The treasure's relation to its lost setting of perishable materials and ritual actions emphasised how the objects ‘activated’ the altar space, highlighting its sacredness as a place for encountering the divine.